Middle-retroauricular Island Flap: A New Axial Flap for Reconstruction of Non-helical Ear Defects - Giovanni Papa, MD, PhD; Chiara Stocco, MD; Zoran Marij Arnež, MD, PhD (Plastic and Reconstructive Surgery, Global Open, 2020)
Background:. Surgical treatment of ear carcinomas needs the selection of the appropriate reconstructive techniques, which depends on the location and the dimensions of the defect after excision of the cancer and the quality of blood supply to the peri-lesional skin. The aim of this study was to evaluate the efficacy and reliability of a new axial island retroauricular flap (middle-retroauricular island flap M-RIF) for coverage of non-helical ear defects with direct donor site closure. Methods:. All patients, from January 2013 to January 2020, with skin tumors of the non-helix region and undergoing a combined skin-cartilage excision with M-RIF local flap reconstruction under local anesthesia, were enrolled in the study. Results:. 18 patients (14 men and 4 women) underwent auricle skin-cartilage excision and M-RIF flap reconstruction. The mean age was 65 years (range, 60–85); the type of primary lesions were 12 BCC and 6 SCC. One flap wound dehiscence and one donor site infection and partial necrosis of the posterior auricular skin occurred; no other complications were recorded. Conclusions:. The M-RIF flap is a valid surgical option when dealing with non-helical defects of the anterior pinna. It allows the reconstruction of the defect of the entire anterior surface of the auricle apart from the helix and the lobe and primary donor site closure.